2012
DOI: 10.1590/s1516-89132012000600020
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation and toxicological evaluation of lubricant oils

Abstract: The aim of this work was to compare different toxicity levels of lubricant oils. The tests were performed using the earthworm (Eisenia andrei), arugula seeds (Eruca sativa) and lettuce seeds (Lactuca sativa), with three types of contaminants (mineral lubricant oil, synthetic lubricant oil and used lubricant oil) for various biodegradation periods in the soil. The toxicity tests indirectly measured the biodegradation of the contaminants. The samples were analyzed at t0, t60, t120 and t180 days of biodegradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 13 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…25 Spilling and leakage of used oil and lubricants can harm the fishes, wildlife and vegetation. 6 Considerable reduction in toxic contamination due to the lubricants is possible if mineral oils are replaced by vegetable oils. However, cold flow properties, oxidative stability and hydrolytic stability are inferior and need improvement for the application of vegetable oil as green lubricants.…”
Section: Introductionmentioning
confidence: 99%
“…25 Spilling and leakage of used oil and lubricants can harm the fishes, wildlife and vegetation. 6 Considerable reduction in toxic contamination due to the lubricants is possible if mineral oils are replaced by vegetable oils. However, cold flow properties, oxidative stability and hydrolytic stability are inferior and need improvement for the application of vegetable oil as green lubricants.…”
Section: Introductionmentioning
confidence: 99%
“…The international agencies for research on cancer, a subsidiary of the World Health Organization, have identified mildly treated or untreated mineral oils as carcinogenic in nature. This is harmful to humans, aquatic life, and nature in general (Tamada et al, 2012). In the case of large spills, the biodegradability of mineral oil is another concern that points toward some environmental problems.…”
Section: Introductionmentioning
confidence: 99%
“…At the end of 20th century, people realize the toxicity and non biodegradability of mineral oils. The spilling and throwing of used mineral oil are real threats for fishes, plants and wild life (Tamada et al, 2012;Aluyor and Ori-jesuee, 2009). The physiochemical properties of sand are changing due to the presence of mineral oils (Kayode et al, 2009).…”
Section: Introductionmentioning
confidence: 99%